The mathematical model of glucose dynamics in blood over 24-hour period - Chaikivska, Yulia; Pasichnyk, Roman; Pasichnyk, Nataliia (Publishing House of Lviv Polytechnic National University, 2015)
The article is concerned with the problem of controlling the glucose concentration in blood with minimal application of invasive measuring. The mathematical model of digestion of recepted glucose, which depends on the volume of consumed carbohydrates (instantaneous, fast, slow) has been developed. The mathematical model is built for long-term observations with the use of specially organized experiments. The blood glucose level depends on the intensity of the effect of insulin, that is why the model of insulin dynamics has been developed either. The accumulated insulin is presented as combination of the insulin produced by the body and the insulin coming from injections. The Levenberg-Marquardt method is used to identify the blood glucose dynamics. У цій статті розглянуто проблему контролю концентрації глюкози в крові із мінімізацією застосування інвазивних вимірювань. Розроблено математичну модель розподілу поступлення глюкози, що залежить від обсягу спожитих вуглеводів (миттєві, швидкі, повільні). Математичну модель побудовано для довготривалих спостережень із використанням спеціально-організованих експериментів. Рівень глюкози в крові залежить від інтенсивності дії гормону інсуліну, тому побудовано модель динаміки інсуліну. Сукупний інсулін представлено як поєднання інсуліну, що виробляється організмом та інсуліну, що поступає з ін’єкцій. Для ідентифікації динаміки глюкози в крові використано метод Левенберга – Маквардта.
Математична модель концентрації глюкози в крові протягом доби
Keywords: nonautonomous model; glucose dynamics; diabetesmellitus; identification; distribution model